(untitled) (Journal of Economic Research & Business Administration, 2018)
In the modern world, it is not enough to manage a company only on the basis of well-known functions and management methods. Every company should function as a system capable of training. In the 21st century, in various socio-economic systems, training, primarily provides for personal development, and becomes an integral part of the managerial process. There are many ways to develop the competence of employees in a company. Among them – is corporate training, as one of the formats of business education. In this case, it is not so much about training personnel as about the personal development of employees, as well as the formation of competences that are necessary for employers. It is no accident that companies that practice corporate training are classified as learning organizations. The purpose of this research is to study the extent of the spread and impact of corporate training on efficiency, as well as the indicators of qualitative growth of companies in the post-Soviet republics.